Witnessing extinction – Cumulative impacts across landscapes and the future loss of an evolutionarily significant unit of woodland caribou in Canada. (June 2015) - Johnson, Chris J.; Ehlers, Libby P.W.; Seip, Dale R.
Highlights: Habitat change is a major driver of species distribution and persistence. We measured habitat loss over 22 years for 5 subpopulations of woodland caribou. Habitat loss was dramatic, correlating strongly with population decline. Abstract: Habitat change is a major driver of species distribution and persistence, but there have been few recorded extinction events for terrestrial mammals across Canada. Currently, we are observing the decline, extirpation, and perhaps extinction of several evolutionarily significant units of woodland caribou ( Rangifer tarandus caribou ), an iconic and cultural keystone species. We used an extensive set of caribou locations (5 subpopulations, 102 animals, 270, 808 GPS-collar locations) collected over 11 years within the Central Mountain Designatable Unit to develop species distribution models that quantified avoidance by caribou of anthropogenic and natural disturbance features. Those empirical relationships allowed us to measure the loss of habitat over a 22-year period and correlate habitat change with measured population decline. The disturbance responses for caribou were complex and varied by season and subpopulation. We modelled a zone of influence for roads (1.75 km), seismic and pipelines (2.5 km), oil and gas features (4.25 km), cutblocks (5.5 km), burns (8.0 km), and coal mines (3.0 km). When the distribution models for each subpopulation were applied to the respective seasonal ranges, we measured a maximum loss in high-quality habitat of 65.9%. The reduction in habitat was strongly correlated with the annual multiplicative growth rate of 5 subpopulations of caribou. At current rates of habitat loss and population decline, these caribou, a significant component of Canada's biodiversity, are unlikely to persist. Although the factors leading to extinction are complex, the cumulative impacts of industrial development are a correlative if not causative factor.